New planting systems to increase apple orchard profitability in Argentina: preliminary results - Raffo Benegas, Maria Dolores; Curetti, Mariela; Calvo, Gabriela; Castro, Andrea Lucia; Villarreal, Patricia; Segatori, Aldo Lorenzo (ISHS, 2025)
Trabajo presentado al XII International Symposium on Integrating Canopy, Rootstock and Environmental Physiology in Orchard Systems. Wenatchee, Washington (Estados Unidos), julio de 2021